Understanding the Relationship between Culturally Engaging Campus Environments and College Students' Academic Motivation - Samuel D. Museus; Kiana Shiroma (MDPI AG, 2022)
Low rates of college completion are a major national dilemma, and one way in which college campuses can increase degree attainment rates is by fostering higher levels of academic motivation among students. This study analyzed the relationship between culturally engaging campus environments and growth in college students' academic motivation. The survey data from a sample of 704 undergraduates enrolled at a public four-year university on the East Coast were analyzed. Bivariate correlations indicate that all nine indicators of culturally engaging campus environments were correlated with stronger academic motivation. When controlling for demographic and high school variables, cultural validation and humanized environments were directly and positively associated with growth in academic motivation. However, post hoc analysis reveals that cultural familiarity, culturally relevant knowledge, cross-cultural engagement, and collectivist orientation were all indirectly associated with motivation gains through cultural validation. The implications of this study for research include the need for research that analyzes these relationships with larger samples from more diverse institutions and utilizes methods that support stronger causal claims. Implications for practice include the importance of maximizing students' access to culturally engaging environments and ensuring that they are designed with anti-deficit approaches that validate students' backgrounds and identities to enhance academic motivation.